Bioenergy value of seed waste from the Mexican date (Phoenix dactylifera L.) industry - Conrado Garcia-Gonzalez; Ricardo Salomón-Torres; Gisela Montero-Alpírez; Benjamín Valdez-Salas; Marcos Alberto Coronado-Ortega; Mario Alberto Curiel-Alvarez; José Ramón Ayala-Bautista; Robert Krueger; Armando Pérez-Sánchez; Ricardo Torres-Ramos; Laura Samaniego-Sandoval (Biotechnologie, Agronomie, Société et Environnement, 2022)
Description of the subject. Date (Phoenix dactylifera L.) seed waste, from the date industry in Mexico, is an attractive source of biomass for bioenergy due to its renewability, availability, and not being otherwise usable.